Parallel computational fluid dynamics : development and applications of parallel technology : proceedings of the Parallel CFD'98 Conference Hsinchu, Taiwan, May 11-14, 1998 /: development and applications of parallel technology : proceedings of the Parallel CFD'98 Conference Hsinchu, Taiwan, May 11-14, 1998. (1999) - Unknown
No abstract available